2019
DOI: 10.1017/s0022149x18001207
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with adultSchistosoma mansonitegument, treated with sub-curative praziquantel, partially protects mice against the infection

Abstract: The tegument of schistosomes is a source of many potential anti-Schistosoma vaccine molecules. This work aimed to assess the protective effects of the adult Schistosoma mansoni tegument treated (TT) with sub-curative praziquantel (PZQ), whether in vivo (in vivo TT) or in vitro (in vitro TT), in murine schistosomiasis. In vitro TT and in vivo TT showed great similarity, and they differed from untreated tegument antigen (Teg) in terms of quantity and quality of protein bands on SDS–PAGE. Two immunization trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Soliman et al (2008) found that worm reduction with CAP was 53.8% due to eggs reduction post immunization. Etewa et al (2014) tested the CAP with 2 types of adjuvants, BCG and was 56.02% & 51.85%, respectively with reduction of eggs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soliman et al (2008) found that worm reduction with CAP was 53.8% due to eggs reduction post immunization. Etewa et al (2014) tested the CAP with 2 types of adjuvants, BCG and was 56.02% & 51.85%, respectively with reduction of eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Each mouse of GIII was immunized subcutaneously with 500 killed cercariae at the right flank (Hsu et al, 1981). A booster dose of 500killed cercaria was subcutaneously injected at right flank after 2 weeks of the 1 st immunization (Etewa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The poor ability of the RA larvae to induce PGE2 and IL10 has been proposed to be responsible for differential capacity for infection compared to normal larvae (Ramaswamy et al 2000 ; Winkel et al 2018 ). IL-10 is released early after exposure to normal larvae (El-Aswad et al 2020 ). Likewise, the level of dermal inflammation and the provoked protective immunity are governed by IL-10/IL-12 balance (Hogg et al 2003 ).…”
Section: Pge2 and Parasite Survivalmentioning
confidence: 99%
“…ELISA for detection of specific IgG, IgG1, IgG2a, IFN--10: Serum levels of specific IgG, IgG1 and IgG2a were measured in serum samples by homemade ELISA technique (El-Aswad et al, 2019). Serum levels of IFN--10 were measured at the 2 times intervals before infection using a solid-phase sandwich ELISA which were purchased from Life Technologies Corporation for IFN--10.…”
Section: Introductionmentioning
confidence: 99%